Processes of Extension Projects of Instituto Tecnológico de Costa Rica and Women Empowerment in Sarapiquí: Reflections about Community Development based on the Perceptions of Five Women - López-Estrada, Patricia (2023)
Introduction. Extension projects promoted at the university level serve as mechanisms for the betterment and growth of the rural communities. These projects might end up being longitudinal, where the constant mentoring and coaching is fundamental to continue helping the communities. This study examined the impact of extension projects that focused on rural tourism and entrepreneurship to a cooperative. Objective. The descriptive study seeks to portray the importance of university extension processes during 2015-2018 regarding community development, based on a qualitative case study of five women in Sarapiquí. Methodology. The methodology was based on a case study as a detailed description. The focus was descriptive (Baxter y Jack, 2008; Flyvbjerg, 2011; Lichtman, 2013). The case study focused on the experiences of five women, who were trained during 2015-2018 in rural tourism and entrepreneurship coordinated by the Instituto Tecnológico de Costa Rica. [Continue reading the article]